Efeito da contaminação por saliva na resistência adesiva de braquetes cerâmicos utilizando uma resina ortodôntica hidrofílica - Lon, Luís Filipe Siu; Schneider, Patrícia Pigato; Raveli, Dirceu Barnabé; Nascimento, Denise Constance; Guariza-filho, Odilon (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
AbstractIntroductionSome fator, such as the presence of saliva, are able to influence the adhesion of the bracket to the tooth enamel during the orthodontic bonding procedure and may cause the adhesive failure.ObjectiveThe aim of this study was to evaluate the shear strength of orthodontic ceramic brackets bonded with Transbond XT and Transbond Plus Color Change to bovine teeth, under saliva contamination and the adhesive failure mode.Material and methodSixty bovine permanent incisors were randomly divided into 4 groups (n=15) according to bonding material and saliva contamination: Group 1 (G1) bonded with Transbond XT with no saliva contamination; Group 2 (G2) bonded with Self Etching Primer and Transbond Plus Color Change with no saliva contamination; Group 3 (G3) bonded with Transbond XT with saliva contamination and Group 4 (G4) bonded with Transbond Plus Color Change with saliva contamination.ResultThe Kruskal-Wallis non-parametric test (p<0,05) was used and showed that G1 differed statistically from G2 and G3. There was no statistical difference between the other groups. The adhesive remnant index (ARI) ranged between 2 and 3 in G1 and between 0 and 1 score in the other groups.ConclusionSaliva contamination decreases the shear bond strength of ceramic brackets bonded with conventional Transbond XT hydrophobic resin. On the other hand, the Transbond Plus Color Change hydrophilic resin associated with a Self Etching Primer, under saliva contamination, provide a sufficient shear bond strength, suitable for their clinical use.

ResumoIntroduçãoAlguns fatores, como a presença de saliva, são capazes de influenciar a adesão do braquete ao dente durante o procedimento de colagem e podem causar falha da resistência adesiva.ObjetivoO objetivo deste estudo foi avaliar a resistência ao cisalhamento de braquetes cerâmicos ortodônticos colados com Transbond XT e Transbond Plus Color Change em esmalte de dentes bovinos, contaminado e não contaminado por saliva, além de analisar o local da falha adesiva.Material e métodoSessenta incisivos bovinos foram divididos aleatoriamente em quatro grupos (n=15), de acordo com o material de colagem e a presença de contaminação: Grupo 1 (G1): colagem com Transbond XT na ausência de contaminação; Grupo 2 (G2): colagem com Self Etching Pimer e Transbond Color Change na ausência de contaminação; Grupo 3 (G3): colagem com Transbond XT na presença de contaminação, e Grupo 4 (G4): colagem com Self Etching Primer e Transbond Color Change na presença de contaminação.ResultadoO teste não paramétrico de Kruskal-Wallis mostrou que G1 diferiu estatisticamente (p<0,05) de G2 e G3. Não houve diferença estatística significativa entre os demais grupos. O índice de adesivo remanescente (IAR) variou entre 2 e 3 no G1 e entre 0 e 1 nos outros grupos.ConclusãoA contaminação por saliva diminui a resistência adesiva ao cisalhamento de braquetes cerâmicos colados com a resina hidrofóbica Transbond XT convencional. Por outro lado, a utilização da resina hidrofílica Transbond Plus Color Change associada ao Self Etching Primer, em ambiente contaminado por saliva, confere resistência adesiva adequada para o seu uso clínico.
Saliva contamination effect on shear bond strength of ceramic brackets with an orthodontic hydrophilic resin
Keywords: Adhesives; orthodontic brackets; shear strength; saliva; Adesivo; braquetes ortodônticos; resistência ao cisalhamento; saliva